The safety and efficacy of supervised exercise on pregnant women with overweight/obesity: A systematic review and meta‐analysis of randomized controlled trials. Issue 2 (9th November 2020) - Muhammad, Harry Freitag Luglio; Pramono, Adriyan; Rahman, Muhammad Nurhadi
Summary: Behavioural modification through physical activity and dietary counselling has been shown to have beneficial effects on pregnant women with overweight/obesity. Whether exercise alone with supervision (ie, supervised exercise) may also benefit for pregnant women with overweight/obesity is still unknown. This systematic review and meta‐analysis aimed to determine the safety and efficacy of supervised exercise on pregnant women with overweight/obesity. PubMed, Cochrane library, Embase (Ovid), CINAHL (EBSCO), and Web of Science were used to search publications using a combination of main keywords "obesity", "exercise", "pregnant women", and "randomised controlled trial". From a total of 740 publications, 11 randomized controlled trials were included. All studies reported no adverse effects of supervised exercise on pregnant women with overweight/obesity. Of interest, this meta‐analysis showed gestational weight gain (GWG) was lower in the supervised exercise group as compared to control (Mean difference 0.88 kg, 95%CI ‐1.73 to −0.03, P = .04). There was a significant effect of supervised exercise on post‐prandial blood glucose (MD: ‐0.24, 95%CI ‐0.47 to −0.01, P = .04) and insulin resistance (HOMA‐IR) (MD: ‐0.18, 95%CI ‐0.30 to −0.05, P = .005). There were no differences in risk of gestational diabetes mellitus, pre‐eclampsia/gestational hypertension, and newborn outcomes (eg, infants birth weight, preterm birth incident, and gestational age) (all P > .05). This meta‐analysis might suggest beneficial effects of supervised exercise on pregnant women with overweight/obesity to prevent excessive GWG, attenuates insulin resistance, and the post‐prandial blood glucose level.